Characterization of the Highly Prevalent Regulatory CD24hiCD38hi B-Cell Population in Human Cord Blood - Esteve-Solé, Ana; Teixidó, Irene; Deyà-Martínez, Angela; Yagüe, Jordi; Plaza-Martín, Ana M.; Juan, Manel; Alsina, Laia (Frontiers in Immunology, 2017)
The newborn's immune system must transition from a sterile haploidentical uterus to the world full of antigens. Regulatory B-cells (Breg; broadly defined as CD19+CD24hiCD38hi) are tolerance-promoters in the adult immune system. They can inhibit IFN-γ and IL-17 production by T-cells and are essential in different conditions, including pregnancy. Breg have still not been well-characterized in umbilical cord blood, where we hypothesize they are pivotal in the achievement of tolerance. We studied CD19+CD24hiCD38hi Breg in healthy umbilical cord blood (hUCB) compared to healthy peripheral adult blood (hAPB). Total numbers of Breg were increased in hUCB compared to hAPB (34.39% vs. 9.49%; p=0.0002), especially in the marginal zone-like B-cell subset, in which the most marked difference could be observed between hUCB and hAPB (60.80% vs. 4.94%; p=0.1). CD24hiCD38hi subset in hUCB produced IL-10 and inhibited T-cell IFN-γ (1.63 vs. 0.95 Stimulation Ratio (SR); p=0.004)) and IL-4 (1.63 vs. 1.44 SR; p=0.39) production. Phenotypically, hUCB Breg-cells presented IgMhiIgDhiCD5+CD10+CD27- markers, similar to those described in hAPB Breg-cells, but they showed increased IgM concentration and decreased expression of CD22 and CD73 markers. Our work characterized the frequency, phenotype, and function of Bregs in hUCB, which may contribute to understanding of immune tolerance during pregnancy, paving the way to a new approach to immune-related diseases in the fetus and the newborn.